Solusi optimal masalah transportasi biaya tetap menggunakan metode pendekatan tangga - Rahayu, Nizmi Fitri; Muhtarulloh, Fahrudin; Nuraiman, Dian (Jurusan Matematika FMIPA Universitas Jember, 2023)
One special case in transportation problems is the problem of fixed cost transportation, where in this transportation problem there are two cost components, namely fixed costs and variable costs. The difficulty encountered when solving the problem of fixed costs is caused by the behavior of these costs which do not depend on the number of units loaded/transported on the route traversed. The purpose of this study is to determine the optimal solution to the fixed cost transportation problem. This research uses Balinski's linear approach, namely the Stairs Approach Method. The case study used is unbalanced data measuring 3x8, where the fixed costs are vehicle rental costs and the variable costs are fuel. The optimal solution obtained is Rp. 11511.411.768.000,- (eleven trillion five hundred eleven million five hundred eleven billion four hundred eleven million seven hundred sixty-eight thousand rupiah). So it can be concluded that the Ladder Approach Method can be used to find the optimal solution to the fixed cost transportation problem. Keywords:Fixed costs, transportation problems, stairs approach method, optimal solutionMSC2020:76N25